Full-speed scalability of the pdomus platform for dhts - Rufino, José (2007)
Domus is an architecture for Distributed Hash Tables (DHTs) tailored to a shared-all cluster environment. Do- mus DHTs build on a (dynamic) set of cluster nodes; each node may perform routing and/or storage tasks, for one or more DHTs, as a function of the node base (static) re- sources and of its (dynamic) state. Domus DHTs also ben- efit from a rich set of user-level attributes and operations. pDomus is a prototype of Domus that creates an environ- ment where to evaluate the architecture concepts and fea- tures. In this paper, we present a set of experiments con- duced to obtain figures of merit on the scalability of a spe- cific DHT operation, with several lookup methods and stor- age technologies. The evaluation also involves a compari- son with a database and a P2P-oriented DHT platform. The results are promising, and a motivation for further work.